The Value of NATO Option for a New Member - Vesa Kanniainen; Staffan Ringbom (Center for Economic Studies and ifo Institute (CESifo), 2015)
The paper introduces a welfarist approach to the national safety of a nation with membership in a defense alliance as an option. The members are risk averse but heterogeneous in their safety classification. There are two public goods as insurance devices, the domestic military budget and the incremental safety provided by the membership in the alliance. The commitment of the alliance in the creation of safety is, however, imperfect. A sufficient condition is stated for the non-membership. Under a positive option value of the membership, several adverse incentive effects shaping the option value are identified, including the incentive to free ride in domestic defense investment and a moral hazard effect in terms of national commitment to the defense effort. The cost of participation is determined in the spirit of the median voter theorem. The alliance equilibrium is shown to be of two potential types, a stable alliance equilibrium with a positive mass and or a degenerate one with one member only. The driving force in the adjustment of the alliance is its size relative to the safety class of the median voter. Expectations of the decision making of the co-members concerning the commitment can result in multiple equilibria.
Keywords: H20; H57; I21; D63; 330; alliance; national security; free riding; safety classification